The importance of cell organelles in the exchange of substances in the body (Texas Journal of Medical Science, 2022)
In this paper, quantitative changes in lipid content in the liver mitochondria were measured at different times after heliotrin was administered to rats to determine the pathogenetic significance of hepatitis in the liver.